Conscientiousness and Motivator Factors: Can they contribute to each other among TVET Teachers of Nepal? - Shrestha, Milan; Dangol, Rita (Journal of Interdisciplinary Studies in Education, 2020)
The conscientiousness and motivator factors are the fundamental concerns of the organizational behavior among TVET school settings. Taking into an account, this study intends to assess the level and examine the influences between conscientiousness and motivator factors among TVET teachers. For these purposes, the researcher employed the post-positivist paradigm with cross-sectional survey approaches and collected information via a questionnaire from 302 TVET teachers under different clusters. Then, the information was analyzed via descriptive and inferential (e.g. correlation and regression analysis) statistics, and further discussed the obtained results by incorporating the social capital theory. This study explored the high conscientiousness and moderate level of motivator factors, and positive correlation between them among teachers. Furthermore, the increment in conscientiousness contributes to enhance the motivator factors and vice versa. The boosting of conscientiousness and motivator factors collaboratively increased the work performances and finally increases the academic achievements of the school.